Managing boundaries in American administration: the collaboration imperative - Kettl, Donald F. (2006)
Boundaries have long played a central role in American public administration. In part, this is because boundaries are central to the administrative process, as they define what organizations are responsible for doing and what power and functions lie elsewhere. It is also because of the nation's political culture and unusual system of federalism, in which boundaries have always been the focus of conflict. Five boundaries have historically been important in the American administrative system: mission, resources, capacity, responsibility and accountability. New forces make managing this boundaries increasingly difficult: political processes that complicate administrative responses, indirect administrative tactics, and wicked problems that levy enormous costs when solutions fail.Working effectively at this boundaries requires new strategies of collaboration and new skills for public managers.Failure to develop this strategies-or an instinct to approach boundaries primarily as political symbolism-worsens the performance of the administrative system. - Reproduced.
Keywords: Public administration - United States; Public administration